Incidence and risk factors for urinary tract infections in the first year after renal transplantation - VELİOĞLU, ARZU; AŞICIOĞLU, EBRU; TİGEN, ELİF; TİNAY, İLKER; ARIKAN, İZZET HAKKI; YEGEN, ŞEVKET CUMHUR; TANIDIR, YILÖREN; TUĞLULAR, ZÜBEYDE SERHAN (PUBLIC LIBRARY SCIENCE, 2021)
Background The most common infections among renal transplant patients are urinary tract infections (UTI). Our main objective in this study is to determine the incidence of UTIs in patients who have undergone renal transplantation in our hospital, to identify the causative microbiological agents, risk factors and determine the effects of UTI on short-term graft survival. Methods Urinary tract infections, which developed within the first year of renal transplantation, were investigated. Patients were compared regarding demographic, clinical, laboratory characteristics and graft survival. Results 102 patients were included in our study. Fifty-three patients (53%) were male and 49 (48%) were female. Sixty-seven urinary tract infection attacks in 21 patients (20.5%) were recorded. Age (p = 0.004; 95% Confidence Interval [CI]: 1.032-1.184), longer indwelling urinary catheter stay time (p = 0.039; 95% Confidence Interval [CI]: 1.013-1.661) and urologic complications (p = 0.006; 95% Confidence Interval [CI]: 0.001-0.320) were found as risk factors for UTI development in the first year of transplantation. Escherichia coli and Klebsiella pneumoniae were the most frequently isolated microorganisms. Of these bacteria, 63.2% were found to be extended spectrum beta lactamase (ESBL) positive. Multidrug resistant microorganisms (MDROs) were more frequent in male patients (32 episodes in males vs. 14 episodes in females, p = < 0.001). UTI had no negative impact on short-term graft survival. Conclusion Our study results represent the high incidence of UTI with MDROs in KT recipients. Infection control methods should be applied even more vigorously especially in male transplant patients since a higher incidence of UTI caused by resistant microorganisms was reported in male patients.
Keywords: KIDNEY-TRANSPLANTATION; RECIPIENTS; EPIDEMIOLOGY; BACTERIA